Chitin binding protein as a possible RNA binding protein in Leishmania parasites. Issue 1 (13th February 2020) - Rashidi, Sajad; Kalantar, Kurosh; Fernandez-Rubio, Celia; Anvari, Enayat; Nguewa, Paul; Hatam, Gholamreza
ABSTRACT: Leishmaniasis includes a broad spectrum of pathological outcomes in humans caused by protozoan parasites from the genus Leishmania . In recent years, proteomic techniques have introduced novel proteins with critical functions in Leishmania parasites. Based on our report of a Chitin binding protein (CBP) in our previous immunoproteomic study, this article suggests that CBP might be an RNA binding protein (RBP) in Leishmania parasites. RBPs, as key regulatory factors, have a role in post-transcriptional gene regulation. The presence of RBPs in Leishmania parasites has not been considered so far; however, this study aims to open a new venue regarding RBPs in Leishmania parasites. Confirming CBP as an RBP in Leishmania parasites, exploring other RBPs and their functions might lead to interesting issues in leishmaniasis. In fact, due to the regulatory role of RBPs in different diseases including cancers and their further classification as therapeutic targets, the emerging evaluation of CBP and RBPs from Leishmania parasites may allow the discovery of novel and effective drugs against leishmaniasis. Abstract : This article suggests that CBP might be an RNA binding protein (RBP) in Leishmania parasites.